Gender Aspect in Accountancy Profession - Anatolievna Mislavskaya, Natalya; Nikolaevna Polenova, Svetlana; Viktorovna Sotnikova, Lyudmila; Nikolaevna Ermakova, Marina (Opción, 2019)
The professional activity of accountants is characterized by the predominan- ce of women that is paradoxical in the context of the existing contemporary androgynous model of society. The aim of the present study was to conduct a comprehensive interdisciplinary analysis of the requirements for emplo- yees of accounting services and identify the causes of gender inequality. The research methodology was based on expert methods of obtaining primary information, namely, testing and questioning. Conclusions were drawn by means of abstraction, generalization, formalization, and synthesis of the data obtained. The research results revealed in the feminist gender stereotype the prevalen- ce of psychological and social characteristics necessary for the successful implementation of professional activities in the field of accounting. The authors justify scientifically the need to preserve the bipolarity of the accounting profession. The drawn conclusions can significantly change the paradigm of education and training of highly qualified specialists in the relevant field of economic knowledge.